(3TQM ebGeGJ GdMQjQjs - (3GHf eXaQ eMeO Hf eMeO Gdecj GdUbdj GdeGdcjs; (3GdMQjQj,J (B516 (3g` s ((3SGde Hf jSde Hf eMahX s)
(3ChdgG (B:s
(3GdebGeI GdChdi GdebGe HaJM Gdeje (B: (3eUOQ ejei Ch ReGf Ch ecGf ef bGe jbhe bjGekG , ZPG hba efJUHkG s
(3BNQgG (B:s
(3hBNQg ai BNQ TQM GdebGeI GdNGeSI hGdYTQjf (B:" (3hMUdJ Ydi GdYhQI Whd TJhJi , jYfi HbjJ Zdi BNQ GdTJGA Ydi Cde GdHQO JeJ HGdNjQ hGdSYGOI Je GdfUa GdChd ef TQM GdebGeGJ dGHf XaQ Gdeci s
(3HgG fXGe GdJYbjHIs
(3cJHJ YfhGf GdebGeI HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs